The impact of uncertainty on farmers’ adoption of straw returning technology in Northwest China - Ge, Yan; Wu, Haixia (Frontiers in Environmental Science, 2023)
Straw returning technology has the potential to not only enhance the crop’s nitrogen of field, as well as be helpful to protect ecological environment and enhancing crop yield. This paper explores the impact of uncertainty on rural households' adoption of straw returning technology using experimental method based on 703 households in wheat region of Loess Plateau, China. The results show that (1) Most of farmers are inclined to risk aversion and ambiguity aversion, and farmers generally have the characteristics of ambiguity aversion. (2) Risk preference as well as ambiguity preference obviously and negatively impact the possibility of the adoption of straw returning technology, and when farmer's risk preference and ambiguity preference increase by 0.1 unit, the probability of adopting straw returning technology will decrease by 19.4% and 17.1%, respectively. (3) When we take the risk preference and ambiguity preference together into account, risk preference have sufficiently large effects on farmers' decision on adopting straw returning technology relative to ambiguity preference. Overall, this research provides a micro foundation and policy recommendations for farmers' straw returning technology promotion in rural China and sheds light upon how the government can formulate relevant policies to promote green environmental development.